Three-point Multi-term Fractional Integral Boundary Value Problems of Fractional Functional Differential Equations with Delay - Sathiyanathan, K.; Krishnaveni, V.; Sivabalan, M. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we study fractional functional differential equations with three-point multi-term boundary conditions. Our method of analysis is based on the reduction of the given system to an equivalent system of integral equations. Existence and uniqueness results are obtained by using Schauder fixed point theorem and contraction principle. An illustrative example is also presented.